Hollow α‐MnS Spheres and Their Hybrids with Reduced Graphene Oxide: Synthesis, Microwave Absorption, and Lithium Storage Properties. Issue 8 (24th June 2013) - Chen, Dezhi; Quan, Hongying; Wang, Guang‐Sheng; Guo, Lin
Abstract Novel α‐MnS hollow spheres (MHSs) have been fabricated successfully by a one‐pot template‐free solvothermal method. The as‐synthesized α‐MnS spheres have diameters of about 3–5 μm and porous shells of thickness about 0.5 μm composed of numerous nanocrystals. The samples were characterized by X‐ray diffraction, scanning electron microscopy, transmission electron microscopy, and nitrogen adsorption. Time‐dependent morphology evolution suggested that transformation of chemical components and Ostwald ripening play vital roles for these hollow structures with a porous shell. The possible formation mechanism for the fabrication of MHSs is proposed. Meanwhile, MHS–reduced graphene oxide (RGO) hybrids have been prepared in the presence of graphene oxide (GO) by using the same procedure. The amount of GO can affect the morphology of α‐MnS crystals in hybrids. The microwave absorption and lithium storage properties of the pure MHSs and MHS–RGO hybrids were studied in detail. Compared with pristine MHSs, the MHS–RGO hybrids possess remarkably enhanced microwave absorption and lithium storage properties. The enhanced microwave absorbing and electrochemical properties are also explained.